2012
DOI: 10.1074/jbc.m112.391060
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium paratuberculosis CobT Activates Dendritic Cells via Engagement of Toll-like Receptor 4 Resulting in Th1 Cell Expansion

Abstract: Background: Mycobacterium avium subsp. paratuberculosis (MAP) is the causative agent of Johne and Crohn diseases. Results: CobT contributes to the development of T cell immunity through the activation of dendritic cells (DC). Conclusion:CobT is a novel DC maturation-inducing antigen that drives Th1 polarized-naive/memory T cell expansion. Significance: CobT can be an important candidate for the development of vaccine and a IFN-␥-based diagnostic tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Another report has also demonstrated that Rv1917c-treated DCs secrete high levels of IL-6, IL-8, and TNF-α as well as IL-10 but not IL-12 and stimulate CD4 + T cells to produce Th2 cytokines [30]. It has been reported that several MAP proteins, including MAP1981c, MAP2541c (malate dehydrogenase), MAPCobT, and MAP1305, also induce DC maturation and Th1 polarization [18,[31][32][33]. However, no reports have examined MAP proteins that induce Th2 polarization through DC maturation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another report has also demonstrated that Rv1917c-treated DCs secrete high levels of IL-6, IL-8, and TNF-α as well as IL-10 but not IL-12 and stimulate CD4 + T cells to produce Th2 cytokines [30]. It has been reported that several MAP proteins, including MAP1981c, MAP2541c (malate dehydrogenase), MAPCobT, and MAP1305, also induce DC maturation and Th1 polarization [18,[31][32][33]. However, no reports have examined MAP proteins that induce Th2 polarization through DC maturation.…”
Section: Discussionmentioning
confidence: 98%
“…We demonstrated that MAP1889c binds TLR4 molecules in DCs. Other MAP proteins, such as MAP1305, CobT, and MAP1989c, induce DC maturation via the TLR4 signaling pathway [32,33]. MAP stimulates bovine mononuclear cells to secrete higher IL-10 production via activation of MAPK-p38 and interactions with TLR2 [11,35].…”
Section: Discussionmentioning
confidence: 99%
“…Ovalbumin (OVA)-specific CD8 ϩ and CD4 ϩ T cells (responders) were obtained from splenocytes of OT-1 and OT-2 mice, respectively. These T cells were stained with 1 M carboxyfluorescein diacetate succinimidyl ester (CFSE; Invitrogen, Carlsbad, CA, USA) as previously described (22). DCs treated with OVA peptide in the presence of 10 g/ml M. abscessus CFA for 24 h were cocultured with CFSE-stained CD8 ϩ and CD4 ϩ T cells at a DC/T-cell ratio of 1:10.…”
Section: Mixed Lymphocyte Reaction (Mlr)mentioning
confidence: 99%
“…Immature mouse bone marrow-derived DCs (BM-DCs) were generated as described previously (22). Briefly, whole bone marrow cells isolated from C57BL/6, Tlr2 Ϫ/Ϫ , and Tlr4 Ϫ/Ϫ mice were washed with serum-free RPMI 1640 medium.…”
mentioning
confidence: 99%
“…avium subsp. paratuberculosis encounters dendritic cells (21,29,30) and subepithelial macrophages (11) in the lamina propria after translocation across the intestinal epithelial layer. Dendritic cells may also transport M. avium subsp.…”
Section: Avium Subsp Paratuberculosis Affects the Integrity Of Thmentioning
confidence: 99%